First report of leaf spot on Gleditsia sinensis caused by Colletotrichum gloeosporioides in China - Li, Pengfei (Plant disease, 2024)
Gleditsia sinensis Lam (Lamarck et al., 1788) is an endemic species widely distributed in China. In Sep. 2022, leaf spot symptoms were observed on G. sinensis in Xuhui district (31◦9'16''N, 121◦26'36''E), Shanghai, China, with an incidence rate of 55% in the examination of 9 trees. The leaves showed typical symptoms of anthracnose with irregular gray-brown spots and sunken areas. For isolation, 5 × 5 mm sections were cut from the lesion edge of 20 infected leaves collected from 2 trees. The surface of the sections was sterilized by immersion in 75% ethanol for 30 s, followed by 5% NaClO for 1 min, rinsed three times with sterile water, and dried on sterile filter paper. These sections were placed on PDA plates incubated at 25°C in darkness. Eighteen isolates with similar colony morphology were obtained and purified by single spore culturing. Two isolates (YKY2301, 2302) from separate trees were further tested. On the 6th day, the colonies had a diameter of 7.6 to 8.4 cm and appeared white to gray-white with aerial hyphae. The colony's central part exhibited an orange hue due to the conidia accumulation, while the undersides displayed an orange-yellow color. The hyphae were hyaline and smooth, with septa and branches, and the conidia were cylindrical with blunt to slightly rounded ends, measuring 13.1 to 18.8 (average 15.9) μm× 4.0 to 6.6 (average 5.4) μm (n=184). From conidia germinated on glass slides, the appressoria measured 5.5 to 6.3 μm ×4.9 to 5.1 μm (n=50) and were nearly spherical or elliptical in shape. These characteristics matched those of the Colletotrichum gloeosporioides species complex (Cannon et al., 2012; Weir et al., 2012). For molecular identification, the genomic DNA was extracted using a modified CTAB method (Luo et al., 2012). Gene fragments including ITS (PP125667, PP125668), GAPDH (PP153428, PP153429), ACT (PP153424, PP153425), TUB2(PP153917, PP190256), and ApMAT (PP153426, PP153427) were obtained by PCR using universal primers (Huang et al., 2022) and sequenced. The sequences exhibited 98.19% to 99.82% identity with the corresponding gene of the type strain C. gloeosporioides IMI356878 (JX010152, JX010056, JX009531, JX010445, JQ807843) in NCBI BLAST. A multilocus Maximum likelihood phylogenetic tree was constructed based on concatenated the five genes by PhyloSuite. It showed that YKY2301, 2302 were on the same branch with C. gloeosporioides. Based on these results, the isolates were identified as C. gloeosporioides. Pathogenicity tests were conducted by mycelial and conidia inoculation. 5 mm mycelial or blank agar plugs were inoculated onto the leaves of 2 healthy trees in a garden (25 to 30 °C), with and without wounds made by toothpick pricking (n≥3 per group). All mycelial inoculated leaves showed leaf spots on the 6th day. Three healthy 2-year-old seedlings were inoculated with either conidia (108 conidia/ml) or water by leaf spray, and maintained in a climate chamber (27 °C, 80% humidity). Inoculated seedlings showed necrotic leaf spots on day 14, and wilted within 3 weeks. The controls in all tests remained asymptomatic. The pathogen has been re-isolated and confirmed by sequencing, thus fulfilling Koch's postulates. This is the first report of leaf spots caused by C. gloeosporioides on G. sinensis in the world. As illustrated by the example of legume pod infection (Gerusa et al., 2019), it poses a potential threat to the fruits of G. sinensis, despite currently only affecting their ornamental value. This report provides basic information for future research